Effect of microbial consortium application on growth and yield of Oryza sativa L. - Aksarah, Aris; Arfan; Bangkele, Lisa Indriani; Zainal; Fahri; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2024)
A group of microorganisms (bacteria, viruses, fungi, and other microbes) working together to perform a specific task is called a consortium. This study aims to study and determine the growth and yield response of rice plants to the application of a consortium of phyllosphere microbes Fm48 and rhizosphere microbes R15. This research has been conducted since from August to November 2021 in the rice fields of Boya Baliase Village, Marawola District, Sigi Regency, Central Sulawesi Province. This study used a one-factor randomized block design method with grouping based on plot height. The treatment that was tried consisted of four levels, that is: Control = Without applied microbes, Fm48 = Applied a consortium of phyllosphere microbes Fm48, R15 = Applied a consortium of rhizosphere microbes R15 and Fm48R15= Applied a consortium of phyllosphere microbes Fm48 and rhizosphere microbes R15. To determine the effect of the treatment being tested, a variance analysis was carried out. Analysis of variance which showed a significant effect, further test was carried out for LSD α = 0.5. The results showed that the treatment of various consortiums of phyllosphere microbes Fm48 and R15 rhizosphere microbes had no significant effect on growth parameters but had a significant effect on the number of hollow grains and grain weight per 1000 rice grains. The consortium of phyllosphere microbes Fm48 and rhizosphere microbes R15 gave the best results for the lowest number of hollow grains and the highest grain weight per 1000 rice grains.